Active filter harmonic compensator with proportional resonant current controller for photovoltaic inverter - Nam, Le Khoa; Lam, Le Hong; Hieu, Trinh Trung; Hieu, Nguyen Huu (Institute of Advanced Engineering and Science, 2024)
The strong development of renewable energy sources (RES), especially distributed energy sources, brings many benefits to the power system. Single-phase photovoltaic (PV) systems are the fastest growing type of distributed energy source worldwide today. Besides the beneficial factors for the distribution power system, the high penetration rate of solar power systems also causes negative impacts, especially power quality issues. PV inverters generate harmonics during the high-frequency switching of semiconductor elements. Traditionally available passive filters are not effective enough to ensure output power quality when the PV system generates power to the distribution grid. Therefore, this study presents the design of a proportional resonant current controller combined with active filter harmonic compensated (PR+HC) for a single-phase PV inverter. This controller, when integrated into traditional PV inverter, will provide better output power quality, contributing to reducing total harmonic distortion (THD) on the distribution grid. This study analyzes the parameters affecting the harmonic attenuation effect of the PR+HC controller, then simulates it on MATLAB Simulink to evaluate the results. The results of the study show that the PR+HC controller is not only effective in reducing the amplitude of odd harmonics, but also operates reliably even when the grid frequency fluctuates widely.